Assessment of Risk Factors Associated With Hospital-Acquired Pressure Injuries and Impact on Health Care Utilization and Cost Outcomes in US Hospitals. (July 2018) - Dreyfus, Jill; Gayle, Julie; Trueman, Paul; Delhougne, Gary; Siddiqui, Aamir
Hospital-acquired pressure injuries (HAPI) are a societal burden and considered potentially preventable. Data on risk factors and HAPI burden are important for effective prevention initiatives. This study of the 2009-2014 US Premier Healthcare Database identified HAPI risk factors and compared outcomes after matching HAPI to non-HAPI patients. The cumulative incidence of HAPI was 0.28% (47 365 HAPI among 16 967 687 total adult inpatients). Among the matched sample of 110 808 patients (27 702 HAPI), the strongest risk factors for HAPI were prior PI (odds ratio [OR] = 12.52, 95% confidence interval [CI] = 11.93-13.15), prior diabetic foot ulcer (OR = 3.43, 95% CI = 3.20-3.68), and malnutrition (OR = 3.11, 95% CI = 3.02-3.20). HAPI patients had longer adjusted length of stay (3.7 days, P < .0001), higher total hospitalization cost (8014, P < .0001), and greater odds of readmissions through 180 days (OR = 1.60, 95% CI = 1.55-1.65). This study demonstrates how big data may help quantify HAPI burden and improve internal hospital processes by identifying high-risk patients and informing best practices for prevention.